2017
DOI: 10.3389/fpubh.2017.00184
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Yoga Practitioners, Motivators, and Yoga Techniques of Choice: A Cross-sectional Study

Abstract: BackgroundThe characteristics of yoga practitioners and factors motivating people to practice yoga have been studied in the US and in Australia. This study aimed to determine the characteristics of yoga users in India, the factors that motivate them to practice yoga, and the yoga techniques of choice.Materials and methodsThe study was a one-time, cross-sectional survey based on convenience sampling. Inclusion criteria were (a) a minimum of 1 week experience of yoga and (b) at least 10 years of age. 14,250 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
6
19
1
Order By: Relevance
“…8 According to various reports in the literature, the most common place to practice yoga is yoga studios. 3,7,17 Similarly, 62.6% of the respondents in our study stated that they practiced in yoga studios. Ross et al (2013) 8 also reported that more yoga contact time (overall duration and/or frequency of practice) was associated with higher likelihood of belief in the health benefits of yoga.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…8 According to various reports in the literature, the most common place to practice yoga is yoga studios. 3,7,17 Similarly, 62.6% of the respondents in our study stated that they practiced in yoga studios. Ross et al (2013) 8 also reported that more yoga contact time (overall duration and/or frequency of practice) was associated with higher likelihood of belief in the health benefits of yoga.…”
Section: Discussionmentioning
confidence: 49%
“…8 Ross et al (2013) 20 also reported that yoga practitioners were mostly female (84.2%) and well-educated, with 90% holding an undergraduate or higher degree. However, a group of yoga practitioners aged 21-44 years in a study conducted in India by Telles et al (2017) 3 was predominantly male (67.3%) with high school education (62.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Penman, Cohen, Stevens, and Jackson [26], for Australian yogis, 61% of the time was spent practicing asana and vinyasa, with the other 39% was spared to the gentler practices of relaxation, pranayama, and meditation. Telles, Sharma, Singh, and Balkrishna [27] later found that the choice of yoga technique differs among nations and between age groups. Whichever their choice, it is reasonable to believe that the style of yoga a yogi adheres to is highly associated with his or her motivation of yoga practice.…”
Section: Yoga Stylesmentioning
confidence: 99%
“…Telles et al, in a cross-sectional survey, had studied the characteristics of yoga practitioners in India in a manner similar to studies previously undertaken in the U.S.A. and Australia. Based on the response to the survey, it was found that yoga practitioners in India are predominantly males, with the chief reason to practice yoga being physical fitness [11] and not disease prevention. However, evidence suggests that yoga plays a pivotal role in changing the physiology of the body.…”
Section: Introductionmentioning
confidence: 99%